Assessment of spatial relationship between groundwater pollution vulnerability and quality indices in Kano, Nigeria - Mohammed Hamza, Salahu; Ahsan, Amimul; Imteaz, Monzur Alam; Mohammad Ali, Thamer Ahmad; Ghazali, Abdul Halim; Mohamed Shariff, Abdul Rashid (Springer Verlag, 2017)
Safeguarding groundwater from pollution is largely a global political decision. These decisions are basically supported by DRASTIC (D=Depth to water, R=Recharge, A=Aquifer media, S=Soil media, T=Topography, I=Impact of vadose zone, C=Hydraulic conductivity) analysis. Furthermore, water quality index (WQI) is an effective tool for groundwater quality evaluation and management. This study identifies the relationship between these two indices [i.e., pollution vulnerability index (PVI) and WQI]. The DRASTIC index of the study area was found to be from 60.4 to 178 characterized by very low, low, medium high, and very high vulnerability constituting of 12.88, 24.38, 34.11, 21.99, and 6.63% of the study area, respectively. In addition, the WQI of the area according to the analyzed parameters is between 10.19 and 55.63. It was established that a good correlation (61%) was found to exist between the two indices; which may be an indication that most pollutants present in the groundwater are likely due to anthropogenic activities on the land surface.